The Latent Digital Divide and Its Drivers in E-Learning among Bangladeshi Students during the COVID-19 Pandemic - Md Badiuzzaman; Md. Rafiquzzaman; Md Insiat Islam Rabby; Mohammad Mustaneer Rahman (Information, 2021)
The devastating COVID-19 pandemic forced academia to go virtual. Educational institutions around the world have stressed online learning programs in the aftermath of the pandemic. However, because of insufficient access to Information Communication Technology (ICT), a substantial number of students failed to harness the opportunity of online learning. This study explores the latent digital divide exhibited during the COVID-19 pandemic while online learning activities are emphasised among students of Bangladesh. It also investigates the digital divide exposure and the significant underlying drivers of the divide. In order to accomplish this, a cross-sectional survey was employed to collect quantitative data, mixed with open-ended questions were utilised to gather qualitative information from the student community. The findings revealed that despite the majority of students having physical access to ICT, only 32.5% of students could attend online classes seamlessly. In total, 34.1% reported data prices as the critical barrier, while 39.8% identified poor network infrastructure as the significant barrier preventing them from participating in online learning activities. Although most students possess physical access to various devices and the Internet, they face the first-level digital divide due to the quality of access and price of cellular Internet. Consequently, they fail to take advantage of physical access, resulting in the third-level digital divide (utility gap), which submerges them into a digital divide cycle. The primary objective of this study is to explore the underlying issues of the digital divide among Bangladeshi students. This will assist relevant stakeholders (e.g., the Bangladesh government, educational institutions, and researchers) to gain necessary insights and theoretical understanding of underlying limitations and emergent directions to arrange adequate support for underprivileged students to undertake essential online learning activities.